Kampung Sindu: Jejak Islam dan Situs Kerukunan di Keramas, Gianyar, Bali - I Nyoman Yoga Segara (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2018)
There are several historical sources that reveal the entry and development of Islam in Bali, both from the studies of historians and Babad Dalem. Base on the field and study documents obtained information that although there are a few differences in interpretation, almost all of these historical sources state that the entry of Islam was not through violence, but was brought by King Gelgel, who migrated due to the collapse of Majapahit. When Gelgel as the epicenter of the kingdom in Bali encountered a setback and a split, Muslim migrants who came from Java, Makassar, and Lombok were employed as soldiers to defend the kingdom from attacks. After the war, the soldiers were given shelter in the form of land supply. They create unique villages according to their ancestral tribes, such as Kampung Jawa, Kampung Bugis, or Kampung Sasak. This article aims to explore the history and the development of Islam in the township in question, one of them Kampung Sindu. Kampung Sindu is one of the Islamic communities of the Sasak tribe, Lombok, which inhabits the catu land in the village of Keramas, Gianyar Regency, Bali. The results of the research shows that they mix in sosial, cultural, and religious life and become an integral part of the village, particularly in the field of palemahan and pawongan. They build harmony sites with totality. Tolerance is maintained based on shared values through local wisdom. They have become Balinese Muslims.Keywords: Kampung Sindu, Keramas Village, Islamic Footprint, Harmony SiteAda banyak sumber sejarah yang menceritakan masuk dan berkembangnya Islam di Bali, baik dari kajian para sejarawan maupun Babad Dalem. Berdasarkan penelitian lapangan dan studi dokumen diperoleh keterangan bahwa meskipun terdapat sedikit perbedaan tafsir, namun hampir semua sumber sejarah menyatakan masuknya Islam tidak melalui jalan kekerasan, tetapi dibawa oleh raja Gelgel, ikut bermigrasi karena runtuhnya Majapahit, dan jalur niaga di pesisir. Saat Gelgel sebagai episentrum kerajaan di Bali mengalami kemunduran dan perpecahan, pendatang Islam yang datang dari Jawa, Makassar dan Lombok banyak dijadikan prajurit untuk melindungi kerajaan dari serangan sesama kerajaan lain serta menghadapi kolonial Belanda. Setelah peperangan, para prajurit itu diberikan tempat tinggal berupa tanah catu dan sampai saat ini masih menjaga hubungan baik dengan keluarga kerajaan. Mereka membangun perkampungan yang unik dan khas, sesuai suku leluhurnya, seperti Kampung Jawa, Kampung Bugis, atau Kampung Sasak. Artikel ini bertujuan untuk menelusuri sejarah dan perkembangan Islam di perkampungan yang dimaksud, salah satunya Kampung Sindu. Kampung Sindu adalah salah satu komunitas Islam dari suku Sasak, Lombok yang mendiami tanah catu kerajaan di desa Keramas, Kabupaten Gianyar, Bali. Hasil penelitian ini menunjukkan bahwa dalam kehidupan sosial, budaya dan agama, mereka berbaur dan menjadi bagian integral dari desa pakraman, khususnya di bidang palemahan dan pawongan. Situs kerukunan mereka bangun dengan totalitas. Toleransi dipelihara berdasarkan nilai bersama melalui kearifan-kearifan lokal. Mereka telah menjadi orang Bali beragama Islam.Kata Kunci: Kampung Sindu, Desa Keramas, Jejak Islam, Situs Kerukunan